Penerapan Sistem Informasi Geografis (SIG) Dalam Kajian Porositas Tanah Pada Wilayah Pesisir Tuban - Pare, Jeremy Rumbaya Kondo; Wibisana, Hendrata; Solin, Dian Purnamawati (Universitas Batanghari Jambi, 2025)
Soil porosity plays an important role in the design of the substructure of a building. Soil porosity itself is one of the characteristics of the soil. By understanding the level of porosity, land management and spatial planning in the future can be carried out more efficiently and quickly. This study aims to calculate soil porosity levels, develop a mathematical model that links soil porosity with satellite image reflectance, and map the distribution of soil porosity levels in the coastal area of Tuban. The research methods include laboratory testing and numerical data processing using the Lagrange polynomial approach. Mapping was performed using ArcGIS software, utilizing Landsat 8 satellite image reflectance data (Band 4 and Band 5) combined with field data. The results of this study show that soil porosity levels in the coastal area of Tuban vary considerably. The mathematical model obtained is derived from a second-degree polynomial equation, y = 83.775x² - 46.752x + 6.8654, with high accuracy, indicated by an average data deviation of 2%. Data points from Google Earth Pro were integrated into ArcGIS to produce thematic maps. These maps visualize the variation in soil porosity distribution through a color gradient.